PENGARUH DER DAN ROA TERHADAP ROE PERUSAHAAN PERTAMBANGAN SUBSEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012 – 2017 - Ryando, Ryando (JURNAL ILMIAH M-PROGRESS, 2020)
This study aims to analyze the effect of the level of debt as measured by the debt to equity ratio (DER)and return on assets (ROA) on return on equity (ROE). The research uses a quantitative approach to thedesign of causality. The study conducted on coal mining sub-sector companies listed on the Indonesia StockExchange for the period 2012 - 2017. The sample selection uses a purposive sampling method to obtain 22company samples. The research data is secondary data, namely audited financial statements and receivedthrough the official website of the Indonesia Stock Exchange. The hypothesis tested using the panel dataregression method. The analysis found that the leverage ratio measured by DER and profitability measuredby return on assets (ROA) harmed ROE, while ROA had a positive impact on ROE.Keywords: return on equity, leverage, debt to equity ratio, return on assets ratio.